THE INFLUENCE OF COMPANY SIZE, KAP SIZE, AND AUDIT COMMITTEE, ON AUDIT FEE: On Banking Companies Listed on the Indonesian Stock Exchange - Muhsin, Muhsin; Suryantini, Suryantini; Elida, Sri Syabanita (Yayasan Education and Social Center, 2024)
This research examines the impact of Company Size (UP), Public Accounting Firm Size (UK), and the Existence of an Audit Committee (KA) on Audit Fees in banking companies listed on the Indonesia Stock Exchange (BEI) during the 2016-2019 period. By using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach via WarpPLS 8.0 software, the main findings show that UP, UK, and KA have a significant effect on Audit Fees. The analysis confirms that company size (UP) is an important factor for auditors in determining the amount of audit fees because it influences the complexity of the audit. In addition, both the size of the Public Accounting Firm (UK) and the existence of an Audit Committee (KA) also influence the size of the auditor's fee, indicating that the selection of a Public Accounting Firm (KAP) and the adoption of an audit committee affect the company's audit fees. The results of this research provide important insights into the financial management of banking companies, especially in managing audit costs and decision making related to internal and external audits. The implications of these findings can help financial managers consider the factors that influence Audit Fees, so that they can manage costs efficiently and make more informed decisions regarding the audit process